A Nanoporous Carbon‐MXene Heterostructured Nanocomposite‐Based Epidermal Patch for Real‐Time Biopotentials and Sweat Glucose Monitoring (Adv. Funct. Mater. 49/2022). (2nd December 2022) - Zahed, Md Abu; Sharifuzzaman, Md; Yoon, Hyosang; Asaduzzaman, Md; Kim, Dong Kyun; Jeong, Seonghoon; Pradhan, Gagan Bahadur; Shin, Young Do; Yoon, Sang Hyuk; Sharma, Sudeep; Zhang, Shipeng; Park, Jae Yeong
Abstract : Hybrid Epidermal Biosensing System In article number 2208344, Jae Yeong Park and co‐workers reported in‐depth investigations of electrophysiological parameters with precise glucose level determination using a butterfly inspired hybrid epidermal biosensing (bi‐HEB) patch. As a portable smart healthcare monitoring system, the NPC@MXene‐based bi‐HEB patch was successfully paired with a miniaturized printed circuit board to assess glucose and electrocardiogram of individuals during exercise.